Wages and international tax competition - Sebastian Krautheim; Tim Schmidt-Eisenlohr (Center for Economic Studies and ifo Institute (CESifo), 2012)
Rent-sharing between firm owners and workers is a robust empirical finding. If workers bargain with firms, information on the actual surplus is essential. When the firm can use profit shifting to create private information on the surplus, it can thereby reduce its wage bill. We study how rent sharing and this wage incentive for profit shifting affect the ability of governments to tax multinational companies in a standard model of international tax competition. We find that if firms only have a tax incentive for profit shifting, rent-sharing decreases the competitive pressure on the large country and leads to higher equilibrium tax rates. When we allow for the wage channel, this result can change. If the wage incentive is sufficiently strong, rent-sharing increases the competitive pressure on the large country, implying a lower equilibrium tax rate.
Keywords: F23; H25; H73; 330; wages; tax competition; rent-sharing; profit shifting; tax havens; private information; Steuerwettbewerb; Multinationales Unternehmen; Erfolgsbeteiligung; Lohnbildung; Gewinnverlagerung; Asymmetrische Information; Steuerwettbewerb; Steueroase; Theorie